2021
DOI: 10.1111/bjhp.12577
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐related decisional conflict in pre‐dialysis chronic kidney disease patients in Singapore: Prevalence and determinants

Abstract: Background. In advanced chronic kidney disease (CKD), patients face complex decisions related to renal replacement modality that can cause decisional conflict and delay. This study aimed to evaluate the prevalence of severe decisional conflict across decision types and to identify the psychosocial and clinical factors associated with decisional conflict in this population.Design. Observational cross-sectional study.Methods. Patients with CKD in renal care were recruited. The Decisional Conflict Scale (DCS), Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Indeed, focusing on improving health literacy skills of patients via improved interpersonal and communication aspects of these healthcare encounters can potentially aid patients in their decision for dialysis modality. Goh et al reported the association of severe treatmentrelated decisional conflict-a state associated with individuals changing their mind, regret, lack of knowledge and blame for bad outcomes, in pre-dialysis chronic kidney disease patients in Singapore and health literacy skills related to communication and engagement with healthcare providers [49,50]. Consequently, a collaborative multi-disciplinary team and patient-centric approach is crucial to provide holistic support for decision-making and avoid pure physician-led paternalism or family-led determination [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, focusing on improving health literacy skills of patients via improved interpersonal and communication aspects of these healthcare encounters can potentially aid patients in their decision for dialysis modality. Goh et al reported the association of severe treatmentrelated decisional conflict-a state associated with individuals changing their mind, regret, lack of knowledge and blame for bad outcomes, in pre-dialysis chronic kidney disease patients in Singapore and health literacy skills related to communication and engagement with healthcare providers [49,50]. Consequently, a collaborative multi-disciplinary team and patient-centric approach is crucial to provide holistic support for decision-making and avoid pure physician-led paternalism or family-led determination [51].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is crucial to elicit patients' preferences and priorities which influences their decision for dialysis The multidisciplinary team will therefore benefit from additional training in shared decision-making, bias awareness and communication skills to support patients in making decisions that are consistent with their values and preferences [28]. Readily eliciting patients' input and active listening in addition to decreasing didactic content can improve the quality of communications by healthcare providers and also foster and hone patients' communicative health literacy skills [50].…”
Section: Elicit Individual Preferences and Prioriɵesmentioning
confidence: 99%
“…We considered these characteristics to be potentially relevant to decisional conflict based on their theoretical or empirical association in past studies. [11][12][13][14][15][16][17]25,26…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…11,12 Although choosing a kidney failure treatment can be characterized similarly, decisional conflict remains poorly understood among adults with advanced CKD. [13][14][15][16] Yet, decisional conflict may result in decisions misaligned with values or preferences; adverse changes in behavior, psychological well-being, and health; and decreased CKD-related treatment satisfaction and patient activation. 14,15,17 Further, unresolved decisional conflict can lead J o u r n a l P r e -p r o o f to undesirable post-decision consequences, including lower treatment adherence and decisional distress.…”
Section: Introductionmentioning
confidence: 99%
“…A small sample report in the US indicated that individuals with lower decision self-e cacy, no predialysis education, lower dialysis knowledge, and perceived lower professional support reported higher decisional con ict when choosing a dialysis modality [16] . Other studies have linked male gender, age (45 or older), low selfe cacy, knowledge, social support, and emotional quality of life (QOL) to higher decisional con ict [17] . Singapore scholar Zack [18] found that the overall prevalence of severe decisional con ict was 27.5% (n = 190), with only the health literacy domains of FCCHL Communicative and HLQ Active Engagement remaining signi cant in the multivariable model.…”
Section: Introductionmentioning
confidence: 99%